El sol sale dos veces sobre el río - Bedoya, Luz María (2023)
A story at the crossroads of a reflection on the possibility of conceptual dismantling of some optical devices of representation and the figure of Alexandra David-Néel –one of the first anarchist, feminist and traveler women in history– in order to wonder, attending to their mutual illuminations and their obscurities, about the powers and impotence of distance.